Anti-PbO-type CoSe film: a possible analog to FeSe superconductors. (15th October 2018) - Liu, Chong; Zheng, Fawei; Shen, Lei; Liao, Menghan; Wu, Rui; Gong, Guanming; Ding, Cui; Yang, Haohao; Li, Wei; Song, Can-Li; He, Ke; Ma, Xu-Cun; et al.
Abstract: Quasi-two-dimensionality is well known as a key electronic and structural element of high temperature superconductivity. Here we prepared ultrathin films of anti-PbO-type CoSe down to the monolayer on a SrTiO3 (001) substrate using molecular beam epitaxy, and investigated their electronic structures by scanning tunneling microscopy, angle-resolved photoemission spectroscopy, and transport measurements in combination with first-principles calculations. We found that the monolayer CoSe had similar band structure and non-ferromagnetism nature with monolayer FeSe on SrTiO3, except for the Fermi level upshift by ∼0.25 eV and weaker electronic correlation with a renormalization factor of 1.7, due to extra electron filling from Co 3d 7 compared with Fe 3d 6 . The results hint that superconductivity might emerge in hole-doped tetragonal CoSe films.